Lacunar lesion of the thalamus: a case report (Jornal Memorial da Medicina, 2021)
In this article, the authors present a computed tomography (CT) image scan of the brain of a 72-year-old patient who, upon waking, noticed numbness in the left hemiface, hemithrunchus, and upper limb. Sensorimotor syndromes are commonly related to vascular infarction of inferolateral artery (ILA) territory, also known as thalamogeniculate pedicle. Usually this pain disturbance happens in right thalamic infarcts having a delayed onset, however, it might be acutely presented..